2020
DOI: 10.1108/jhti-01-2020-0001
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of environmental engagement and environmental learning behaviour

Abstract: PurposeRecent studies have classified ecotourism behaviour into specific components like site-specific ecological, pro-environmental and environmental learning behaviour. However, the role of materialism in generating these types of behaviour is not clearly understood. Materialism might also affect tourists' environmental engagement. Hence, this study embarks on exploring these research gaps.Design/methodology/approachAll the constructs were operationalized as first-order factors based on extant scales of meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 65 publications
0
9
0
3
Order By: Relevance
“…Other studies, however, find support in the other direction, namely that happiness or the motivation to be happy may drive people to accumulate and consume in unsustainable ways. For example, as individuals obtain material goods, they gain the status of success attached to those materials goods (Manoj et al 2020). Consequently, they often link their happiness and life satisfaction to those goods and the attainment of more goods (Calìope Sobreira et al 2020).…”
Section: Happiness and Sustainability: Seminal Workmentioning
confidence: 99%
“…Other studies, however, find support in the other direction, namely that happiness or the motivation to be happy may drive people to accumulate and consume in unsustainable ways. For example, as individuals obtain material goods, they gain the status of success attached to those materials goods (Manoj et al 2020). Consequently, they often link their happiness and life satisfaction to those goods and the attainment of more goods (Calìope Sobreira et al 2020).…”
Section: Happiness and Sustainability: Seminal Workmentioning
confidence: 99%
“…At the same time, due to the insufficient understanding of the role of plant protection in tourism, the surrounding environment has deteriorated and the risk of large-scale outbreaks of pests and diseases has increased. From the academic point of view, ecotourism mainly focuses on planning, economy and ecology, but there are few theoretical studies on the role of plant protection on ecotourism (Awasthi and Bollas, 2020;Manoj et al, 2020). The construction of 10.3389/fpls.2022.993838 ecological agriculture has laid a good material foundation and pollution-free security for the development of tourism.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it is not well known why, how or if students come to embody a sustainable lifestyle. A small subset of research within the broader population and student populations suggests that sustainability behaviors are distinctly psychological and motivational matters (Cloutier et al , 2014; Mandliya et al , 2020; Manoj et al , 2020). Hence, in this paper, we aim to better understand the relationship between one aspect of psychological-happiness and motivational life-academic achievement on sustainability behaviors among students in a Mexican higher education institution, one of the world’s top sustainable universities.…”
Section: Introductionmentioning
confidence: 99%
“…Somewhat in line with these ideas, a recent analysis of the 2013 China General Social Survey found that community-level pollution and environmental degradation via socioeconomic development was positively associated with the self-reported happiness (SRHP) of high-income groups (Gu et al , 2017). Thus, materialism, consumption and attaching happiness to extrinsic sources appear to be a constraint to environmental engagement as well as to environmental learning behavior (Manoj et al , 2020).…”
Section: Introductionmentioning
confidence: 99%